Performance profile and game-related statistics of FIBA 3x3 Basketball World Cup 2017 - Conte, D.; Straigis, E.; Clemente, F. M.; Gómez, M. A.; Tessitore, A. (Biology of Sport, 2019)
The study aimed to characterize the performance profile of 3x3 basketball and particularly to assess: a) the differences between games in live time (LT) and stoppage time (ST) phases and their ratio, and b) the game-related statistics and derived game indicators differentiating between winning and losing teams. Eight games [quarterfinals, semifinals and finals (1st and 3rd place)] of the FIBA 3x3 basketball world cup (Serbia, 17th-21st June 2017) were analysed. The LT and ST phases were categorized into three phase durations: 1-20 s, 21-40 s, >40 s. The LT/ST ratio was calculated. The game-related statistics and derived parameters were assessed through video-based notational analysis methods, and differences between winning and losing teams were calculated using a mixed linear model. The results revealed no statistically significant differences in the distribution of LT and ST phases between games, with an LT/ST ratio of 0.92±0.13. Moreover, winning teams showed a significantly higher (p<0.05) number of free throws made and attempted, team offensive ratings, and recovered balls per possession compared to losing teams. Conversely, winning teams revealed significantly lower (p<0.05) values for turnover, rebound (offensive, defensive and total), offensive rebound percentage and team defensive rating compared to losing teams. These results provide coaches and practitioners with novel and applied information regarding the performance profile of 3x3 basketball to optimize training sessions, which should be characterized by short live time phases and a work-to-rest ratio ~1 and focused on developing the ability to avoid turnovers and increase the recovered balls per possession, minimizing the scoring possibilities for the opponent team.